Molecular Tuning of Actin Dynamics in Leukocyte Migration as Revealed by Immune-Related Actinopathies - Kamnev, Anton; Lacouture, Claire; Fusaro, Mathieu; Dupré, Loïc (Frontiers in Immunology, 2021)
Motility is a crucial activity of immune cells allowing them to patrol tissues as they differentiate, sample or exchange information, and execute their effector functions. Although all immune cells are highly migratory, each subset is endowed with very distinct motility patterns in accordance with functional specification. Furthermore individual immune cell subsets adapt their motility behaviour to the surrounding tissue environment. This review focuses on how the generation and adaptation of diversified motility patterns in immune cells is sustained by actin cytoskeleton dynamics. In particular, we review the knowledge gained through the study of inborn errors of immunity (IEI) related to actin defects. Such pathologies are unique models that help us to uncover the contribution of individual actin regulators to the migration of immune cells in the context of their development and function.